PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN E-BOOK DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MAHASISWA - Sri Lestari Manurung (Universitas Negeri Medan, 2021)
Abstract: This research is a Classroom Action Research (CAR) which aims to improve students' creative thinking skills by applying the Problem Based Learning (PBL) learning model assisted by e-books.In this study, the research subjects were students of the Mathematics Education Study Program class DIK-E 2021 at UNIMED, totaling 42 people. This research was conducted in 2 cycles by going through 4 (four) stages, namely: planning, implementation, observation, and reflection. Data analysis was carried out by descriptive of the average and percentage of students' overall completeness. The results of the research from the application of the PBL learning model in the set and logic courses can be concluded that there is an increase in students' creative thinking skills. This increase can be seen from the average value of the class has increased, namely from the pre-cycle results of 66.72 in the first cycle the class average rose to 70.54 and in the second cycle it rose to 77.43. In the pre-cycle the percentage of students' overall completeness was 18% or 7 of 42 students. In the first cycle the overall percentage of students' completeness increased to 56% or 24 of 42 students, then in the second cycle it increased again to 88% or 37 of 42 students. Based on the description, it can be concluded that there is an increase in students' creative thinking skills which can be seen from the pre-cycle, Cycle I and Cycle II stages. Thus, the application of the PBL learning model assisted by e-books can improve students' creative thinking skills in the set and logic courses.Keywords: PBL Model, E-book, Creative Thinking AbilityAbstrak: Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang bertujuan untuk meningkatkan kemampuan berpikir kreatif mahasiswa dengan menerapkan model pembelajaran Problem Based Learning (PBL) berbantuan e-book. Pada penelitian ini yang menjadi subjek penelitian adalah mahasiswa prodi Pendidikan matematika kelas DIK-E 2021 di UNIMED, yang berjumlah 42 orang. Penelitian ini dilakukan sebanyak 2 siklus dengan melalui 4 (empat) tahapan, yaitu: perencanaan, pelaksanaan, observasi, dan refleksi. Analisis data dilakukan dengan deskripif dari rata-rata dan persentase ketuntasan keseluruhan mahasiswa. Hasil penelitian dari penerapan model pembelajaran PBL pada mata kuliah himpunan dan logika dapat disimpulkan bahwa adanya peningkatan kemampuan berpikir kreatif mahasiswa. Peningkatan ini dapat dilihat dari nilai ratarata kelas mengalami peningkatan yaitu dari hasil pra siklus sebesar 66,72 pada siklus I rata-rata kelas naik menjadi 70,54 dan pada siklus II naik menjadi 77,43. Pada pra siklus persentase ketuntasan keseluruhan mahasiswa sebesar 18% atau 7 dari 42 mahasiswa. Pada siklus I persentase ketuntasan keseluruhan siswa meningkat menjadi 56% atau 24 dari 42 mahasiswa, kemudian pada siklus II meningkat kembali menjadi 88% atau 37 dari 42 mahasiswa. Berdasarkan uraian tersebut, dapat disimpulkan bahwa adanya peningkatan kemampuan berpikir kreatif mahasiswa yang dapat dilihat dari tahap pra siklus, Siklus I dan Siklus II. Dengan demikian penerapan model pembelajaran PBL